Development of novel applications of optical amplifiers in optical communication networks - Guo, Ning (2012)
Optical amplifier is a key component in current and future optical communication networks. It can not only provide amplification to incoming optical signals but also serve as an all-optical signal processing component. There are three categories of optical amplifiers: doped fiber amplifier (mainly erbium dope fiber amplifier (EDFA)), semiconductor optical amplifier (SOA) and Raman fiber amplifier (RFA). EDFA has larger gain, lower pump power and generally amplifies C and L band signals. While, SOA has medium gain, larger bandwidth, and higher noise figure. Most importantly, it has high nonlinearity which is very useful in all-optical signal processing. RFA requires larger pump power and has lower gain. But the bandwidth is flexible, which is determined bypump wavelength. And it has low noise figure comparing with the others. This thesis focuses on developing novel applications of optical amplifiers in future alloptical communication networks. A detailed study on SOA gain characteristics has been done to find the origin of discrepancy between experimental measurements and simulations results given by the well-known formula. Then a modified formula which includes an additional internal loss term is proposed. It shows more accurate description on SOA gain characteristics and is proved to be able to work with different SOAs. A novel configuration of all-optical switch utilizing nonlinear polarization rotation (NPR) in SOA is then proposed. And the switching of a data packet at 2.5 Gb/s is demonstrated experimentally with 20 dB extinction ration obtained. Furthermore, a novel configuration of fiber loop type all-optical buffer is proposed based on the switch. Theoretical investigation has been carried out to analyze buffering results of data packets mixed with microwave signal up to 40 GHz. Thus the parameters have been optimized to obtain a buffering time of 600 ns for 40 GHz microwave signal. Next, a hybrid C+L band pump which combines EDFA and RFA is presented. It utilizes residual pump power left from RFA for pumping of EDFA. Therefore, there is only one pumping laser diode (LD), so it is energy efficient. Moreover, an array of fiber bragg gratings (FBGs) together with dispersion compensating fiber (DCF) segments optimally compensates chromatic dispersion during transmission for all the C+L band channels. In addition, the gain fluctuation could be suppressed greatly from 6.5 dB to 0.2 dB by adjusting the reflectivities of individual FBG.